Dysfunction of brain pericytes in chronic neuroinflammation. Issue 4 (April 2016) - Persidsky, Yuri; Hill, Jeremy; Zhang, Ming; Dykstra, Holly; Winfield, Malika; Reichenbach, Nancy L; Potula, Raghava; Mukherjee, Abir; Ramirez, Servio H; Rom, Slava
Brain pericytes are uniquely positioned within the neurovascular unit to provide support to blood brain barrier (BBB) maintenance. Neurologic conditions, such as HIV-1-associated neurocognitive disorder, are associated with BBB compromise due to chronic inflammation. Little is known about pericyte dysfunction during HIV-1 infection. We found decreased expression of pericyte markers in human brains from HIV-1-infected patients (even those on antiretroviral therapy). Using primary human brain pericytes, we assessed expression of pericyte markers (α1-integrin, α-smooth muscle actin, platelet-derived growth factor-B receptor β, CX-43) and found their downregulation after treatment with tumor necrosis factor-α (TNFα) or interleukin-1 β (IL-1β). Pericyte exposure to virus or cytokines resulted in decreased secretion of factors promoting BBB formation (angiopoietin-1, transforming growth factor-β1) and mRNA for basement membrane components. TNFα and IL-1β enhanced expression of adhesion molecules in pericytes paralleling increased monocyte adhesion to pericytes. Monocyte migration across BBB models composed of human brain endothelial cells and pericytes demonstrated a diminished rate in baseline migration compared to constructs composed only of brain endothelial cells. However, exposure to the relevant chemokine, CCL2, enhanced the magnitude of monocyte migration when compared to BBB models composed of brain endothelial cells only. These data suggest an important role of pericytes in BBB regulation in neuroinflammation.